Electronic structure and magneto-optical Kerr effect in the compound UCuP₂ - Horpynyuk, O.; Nemoshkalenko, V.V.; Antonov, V.N.; Harmon, B.N.; Yaresko, A.N. (Физика низких температур, 2002)
The optical and magneto-optical (MO) spectra of the fernary compound UCuP₂ are investigated from first principles, using the fully relativistic Dirac linear-muffin-tin-orbital band structure method and density-functional theory in the local spin-density approximation. Within a band-like description of the 5f electrons, good agreement with the measured MO spectra is obtained. The origin of the Kerr rotation in the compound is examined.